The Effects of Housing Density on Social Interactions and Their Correlations with Serotonin in Rodents and Primates - Lee, Young-A (Sci Rep, 2018)
Population density has been suggested to affect social interactions of individuals, but the underlying neural mechanisms remain unclear. In contrast, neurotransmission of monoamines such as serotonin (5-HT) and dopamine (DA) has been demonstrated to play important roles in social behaviors. Here, we investigated whether housing density affected social interactions of rodents and non-human primates housed in groups, and its correlations with monoamines. Japanese macaques exhibited higher plasma 5-HT, but not DA, concentrations than rhesus macaques. Similarly, C57BL/6 mice exhibited higher plasma and brain tissue 5-HT concentrations than DBA2 mice. Under crowding, C57BL/6 mice and Japanese macaques exhibited more prominent social avoidance with mates than DBA2 mice and rhesus macaques, respectively. Although DBA2 mice and rhesus macaques in crowding exhibited elevated plasma stress hormones, such stress hormone elevations associated with crowding were absent in C57BL/6 mice and Japanese macaques. Administration of parachlorophenylalanine, which inhibits 5-HT synthesis, increased social interactions and stress hormones in C57BL/6 mice under crowding. These results suggest that, animals with hyperserotonemia may exhibit social avoidance as an adaptive behavioral strategy to mitigate stress associated with crowding environments, which may also be relevant to psychiatric disorder such as autism spectrum disorder.